The Dominance of the Daycare Environment in Early Childhood Care and Its Implications for the Formation of Children’s Self-Identity - Musoheh musoheh (Qualitative Research in Early Childhood Education, 2026)
Social and economic changes in modern families have led to an increased use of daycare as a form of early childhood care. Many children spend more time in daycare than at home with their parents, making the daycare environment a dominant caregiving context in their lives. This condition has the potential to influence the process of self-identity formation in early childhood, which is still in its initial developmental stage. This study aims to understand how the dominance of the daycare environment affects the formation of self-identity in early childhood. The study employs a qualitative approach using structured observation techniques of young children at a daycare institution. Participants were selected through purposive sampling based on the duration of children’s attendance at daycare. Data collection focused on children’s self-expression, social interaction patterns, and emotional responses in daily caregiving activities. Data analysis was conducted using thematic analysis to identify patterns in children’s self-identity formation. The findings indicate that children tend to construct their self-identity based on the norms, relationships, and expectations that dominate the daycare environment. Children adjust their behavior and self-expression in accordance with caregiving patterns experienced repeatedly. The findings emphasize the importance of continuity between home and daycare relationships in supporting healthy self-identity formation in early childhood.